Inclusive preschool education for all children - Nadifa, Milatun; Marbun, Marlina; Zulvani, Nadia Vina; Sunarni, Sunarni (Universitas Islam Negeri Raden Intan Lampung, 2024)
Background: Inclusive preschool education is very important for children in Indonesia, including children with special needs. However, there are still many challenges faced, such as limited access, variations in education quality, and lack of policy support.Aim: This research aims to map the condition of inclusive preschool education in Indonesia, identify supporting and inhibiting factors, and provide policy recommendations that can improve the quality and accessibility of inclusive preschool education.Method: This research uses a Systematic Literature Review (SLR) with an analysis of 24 relevant articles with a time limit of 2020 to 2024.Results: The novelty of this research lies in its comprehensive analysis based on the latest data on inclusive preschool education in Indonesia, which previous research has not specifically explored at the preschool level. From the analysis it is revealed that there are still gaps in the implementation of inclusive preschool education. To improve inclusive preschool education, adequate budget allocation, teacher training, curriculum development based on individual children's needs, cross-sector collaboration, infrastructure adaptation, and development of an inclusive culture are needed. Government support, strong commitment, and the active role of parents, schools, teachers, and the community are also considered important in creating an inclusive educational environment. Policy recommendations include cross-sector collaboration, infrastructure adaptation, inclusion awareness campaigns, regulatory development, and increasing the accessibility of inclusive preschool education.Conclusion: The conclusion of this research shows that with the right strategy and adequate support, inclusive preschool education in Indonesia can be improved significantly so that every child has the same right to quality education.